Industrial Training Report: Perpustakaan Sultanah Nur Zahirah Universiti Malaysia Terengganu / Suhaili Mohd - Mohd, Suhaili (Faculty of Information Management, 2016)
This Industrial Training report is about my training at Sultanah Nur Zahirah Library or Perpustakaan Sultanah Nur Zahirah (PSNZ). This report contains the information about background, function, and organization chart and department structure. All the training activities during my industrial training that started from 1st August until 29 December 2016 also had been written in this report. Skills, knowledge, lesson learnt and experience that I get from the training also included in this report. During the practical training, I had the tasks that are need to do and I can apply it into the real working environment. I also mention my special project which is designing the signage for PSNZ library. The good training and experience during the industrial training need to be used in future.